USE OF STEAM EDUCATIONAL TECHNOLOGIES IN PRIMARY SCHOOL CLASSES AS A RELEVANT PEDAGOGICAL ISSUE - Madina Xaydarova (Research Focus International Scientific Journal, 2024)
The integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education in primary school natural science teaching is essential for developing competencies that equip students with critical 21st-century skills. This paper explores the didactic requirements necessary for the effective formation of STEAM competencies in young learners. It examines the interdisciplinary teaching strategies that blend scientific knowledge with technology, engineering, arts, and mathematics, and highlights key pedagogical approaches such as project-based learning, inquiry-based teaching, and the integration of technology. The study also identifies the challenges educators face, including resource limitations, insufficient teacher training, and rigid curriculum frameworks.